2022
DOI: 10.3390/genes13081345
|View full text |Cite
|
Sign up to set email alerts
|

McCune-Albright Syndrome in Infant with Growth Hormone Excess

Abstract: Background: McCune-Albright is a rare syndrome, caused by mutation of the GNAS1 gene, and is characterized by an appearance of multiple endocrinopathies, most commonly premature puberty, polyostotic fibrous dysplasia and skin changes called cafe au lait macules. Case report: We present the case of a patient who is, to the best of our knowledge and after extensive review of literature, the youngest McCune-Albright syndrome patient with growth hormone excess, diagnosed at 8.9 months of age. An extensive diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…Café-au-lait spots are seen in 53-95% of MAS cases with the Several other endocrinopathies and other tissue involvement have been reported in the literature. 1,7 Hyperthyroidism was present in our patient. Hyperthyroidism is common in 10%-30% of MAS patients.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Café-au-lait spots are seen in 53-95% of MAS cases with the Several other endocrinopathies and other tissue involvement have been reported in the literature. 1,7 Hyperthyroidism was present in our patient. Hyperthyroidism is common in 10%-30% of MAS patients.…”
Section: Discussionmentioning
confidence: 46%
“…Multiple endocrinopathies, early puberty, polyostotic fibrous dysplasia, which causes deformities and pain in the legs, spine, and face, and skin alterations in the form of café au lait macules are all signs of McCune-Albright Syndrome. 1 Although complete information on the prevalence of MAS is not yet known, it is estimated that it affects between 1/100,000 and 1/1,000,000 worldwide. Contrarily, information on skeletal abnormalities brought on by MAS in the form of fibrous dysplasia has been widely published; it is estimated that this condition accounts for more than 7% of benign bone tumor cases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that tissue samples with FD produce elevated basal levels of IL-6, a cytokine that mediates osteoclastogenesis, causing increased bone resorption in the affected bone [4][5][6]. The endocrine pathways in which the signaling of their hormones and receptor proteins are ligand-dependent, such as LH, FSH, TSH, GHRH and ACTH, show hyperfunction, resulting in the characteristic endocrinological alterations of the syndrome [7][8].…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…The endocrine pathways in which the signaling of their hormones and receptor proteins are ligand-dependent, such as LH, FSH, TSH, GHRH and ACTH, show hyperfunction, resulting in the characteristic endocrinological alterations of the syndrome [7,8].…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%